Efforts to Exterminate Money Politics and Build an Integrity Based Democracy in Bireuen Regency - Qadafi, Muammar; Novialdi, Risky; Maulana, M Romi (Department of Government Studies, Universitas Syiah Kuala, 2025)
In Bireuen Regency, as in many other regions of Indonesia, money politics has become a significant issue. This is evident in various corruption cases involving politicians and government officials. The repercussions include policies that often disregard public interest, instead prioritizing the agendas of specific political factions. This problem persists due to the cultural entrenchment of money politics, which has fostered public skepticism toward politics in Bireuen Regency. Consequently, systematic and comprehensive efforts are needed to combat money politics and establish an integrity-based democracy in Bireuen. The objective of this study is to outline measures that can be taken to counter money politics and build an integrity-driven political environment in Bireuen. Adopting a phenomenological approach, this research will be conducted in several phases, including preparation, implementation, and evaluation. The findings reveal that three key stakeholders play a crucial role in safeguarding democratic integrity and countering money politics in Bireuen: the government as the election organizer, regional leadership candidates, and the public. Should any of these parties engage in malpractice, it would adversely impact the image and quality of democracy in Bireuen Regency.